Self-centered spouse : help for chronically broken marriages - Hambrick, Brad, 1977- (Phillipsburg, New Jersey : P&R Publishing, 2014)
"Anyone in a marriage knows that we are all self-centered spouses who are married to self-centered spouses. But when this all-too-common sin becomes severe and chronic, it results in a marital environment of abuse or neglect---leaving the spouse on the receiving end feeling trapped and hopeless. But how might this outlook change if we knew that Jesus addressed just such chronically broken relationships? Brad Hambrick examines Jesus' teachings about relationships to show us how we can turn the other cheek while keeping away from unhealthy and destructive paths. He identifies different types of self-centered spouses to show us what we are dealing with, shares strategies for interacting with them, and points to evidences of genuine change to bring hope to anyone living with a chronically self-centered spouse.."--from publisher description.
Keywords: Marital conflict; Selfishness; Marriage -- Religious aspects -- Christianity; Bible -- Matthew VII, 1-6 -- Criticism, interpretation, etc